Use of Blockchain to Improve Case Studies in Food Supply - Haryanto; Fiananda, Rio Argi; Shilvia Wanri; Sunarsih (Blockchain Frontier Technology, 2022)
The current food supply is a linear economic model that directly or indirectly fulfills needs. However, this model has several weaknesses, such as the relationship between members of the supply chain or the lack of information to consumers about the origin of the product. In this paper we propose a new supply chain model via blockchain. This new model enables the concept of a circular economy and removes many of the disadvantages of the current supply chain. To coordinate all the transactions that occur in the food supply, a multi-agent system is created for this paper.